Immobilized Yeast for Production of Ethanol from Molasses (Journal of the College of Basic Education, 2023)
The production of ethanol from cane molasses by Ca-alginate immobilized Saccharomyces cerevisiae in shaking incubator was studied. The temperature was 30C and the shaking rate was 150 rِِِِ/m. Maximum ethanol (4.62%), theoretical yield (82.9%) and volumetric productivity (10.16 gl/1) were obtained from the cane molasses medium containing 10.90% total sugar with 2.0-2.4 mm diameter beads prepared from 2% (w/v) sodium alginate solution added dropwise to 1000 ml of 2% CaCl2 . Lower ethanol concentration (3.94%), theoretical yield (70.7%) and productivity (8.67 g/1) were obtained.